Copping mechanism of the displaced population by the Riverbank Erosion of the Meghna River at Haimchar Upazila, Chandpur District, Bangladesh - Md. Abu Taleb; Md. Humayun Kabir (Universiti Malaysia Perlis (UniMAP), 2011)
The Second International Conference on the Roles of Humanities and Social Science in Engineering (ICoHSE 2010) organized by Universiti Malaysia Perlis (UniMAP), 12th - 14th November 2010 at Bayview Beach Resort, Penang, Malaysia.